2014
DOI: 10.1007/s11255-014-0769-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pentoxifylline on penile cavernosal tissues in ischemic priapism-induced rat model

Abstract: The results of the present study showed that ischemic priapism caused damage in the penile tissues of rats, and treatment with pentoxifylline reduced the harmful effects of ischemic priapism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Sustained NO releasing compounds have also been shown to normalize activated eNOS and other biochemical elements of erection signaling in mouse models of priapism (37). In a rat model of ischemic priapism, treatment with pentoxyfylline, a non-selective PDE inhibitor, reduced collagen density in the corpus cavernosum, possibly through mechanisms relating to inhibition of TGF-β (58). Sildenafil may provide a vasculoprotective effect through increased expression of eNOS and inhibition of NADPH oxidase, the enzyme responsible for the production of the free radical superoxide (39).…”
Section: Epidemiologymentioning
confidence: 99%
“…Sustained NO releasing compounds have also been shown to normalize activated eNOS and other biochemical elements of erection signaling in mouse models of priapism (37). In a rat model of ischemic priapism, treatment with pentoxyfylline, a non-selective PDE inhibitor, reduced collagen density in the corpus cavernosum, possibly through mechanisms relating to inhibition of TGF-β (58). Sildenafil may provide a vasculoprotective effect through increased expression of eNOS and inhibition of NADPH oxidase, the enzyme responsible for the production of the free radical superoxide (39).…”
Section: Epidemiologymentioning
confidence: 99%
“…This agent had facilitated recovery of erections in a rat model of erectile dysfunction post prostatectomy [118]. In a recent study, pentoxifylline was able to reduce collagen density in an ischemic-induced priapism rat model [119]. The potential benefits of an agent with such an effect are great and this agent requires further studies.…”
Section: Priapism Treatmentmentioning
confidence: 99%
“…[12] Conversely, Costa et al found significantly more collagen and less CCSMC in the corpus cavernosum of IP patients compared to those of normal males. Similarly, others demonstrated significant lower CCSMC/collagen in rats after IP [13,14]. Damaged endothelial continuity could be also found [14].…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, others demonstrated significant lower CCSMC/collagen in rats after IP [13,14]. Damaged endothelial continuity could be also found [14].…”
Section: Discussionmentioning
confidence: 83%